A new controllable adaptive biasing linearization technique for a CMOS OTA and its application to tunable Gm-C filter design. Issue 9 (September 2015) - Rezaei, Farzan; Azhari, Seyed Javad
Abstract This paper presents a new linearized operational transconductance amplifier which uses a fully controlled adaptive biasing scheme. The differential input voltage is sensed through a squarer circuit and is compared with a controllable reference voltage to create appropriate auxiliary tail currents. The proposed adaptive biasing circuit can be adjusted to make best linearization for each tuning condition of OTA. While the adaptive biasing circuit consumes a little portion (about 13%) of the total power consumption (about <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frffd16" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />475μW</alternatives>), it significantly reduces the third-order nonlinearity of OTA׳s output current in whole of its tuning ranges. By applying a two-tone 0.6 Vp-p input voltage at 20 MHz, IM3 is degraded by more than 13 dB throughout the transconductance tuning range from <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frfg90k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />8.2μA/V</alternatives> to <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frfg3b0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />47μA/V</alternatives>. Proposed OTA is employed to implement a wide tunable Gm-C filter. The cutoff frequency of low-pass filter is tunable from 584 kHz to 10.6 MHz, thus, it covers several standards of wireless applications. IIP3 of filter is 22.3 dBm, 19 dBm and 17.4 dBm, respectively, for Bluetooth, UMTS and IEEE 802.11a/g standards. The OTA and Gm-C filter are designed and simulated in 0.18-μm TSMC CMOS technology with Hspice simulator. Monte Carlo and corner case simulations show the good robustness of proposed circuits against the fabrication errors.